KONFLIK BATIN TOKOH MORIGUCHI YUUKO DALAM FILM CONFESSION KARYA TETSUYA NAKASHIMA - Ni Luh Kristy Ariani; Wayan Nurita; Anak Agung Ayu Dian Andriyani (Jurnal Daruma : Linguistik, Sastra dan Budaya Jepang, 2022)
The research "The Inner Conflicts of Moriguchi Yuuko's Character in Tetsuya Nakashima's Confession Film: A Study of Literary Psychology" was motivated by curiosity about what kind of inner conflicts the character Moriguchi Yuuko experienced during his confession. This type of research is descriptive-qualitative research. The source of data used in this research is the Confession film and the character analyzed for the conflict is the character Moriguchi Yuuko. The theory used to analyze the data is Kurt Lewin's field theory. The data collection method used in this research is the library research method and note-taking method, namely by looking for data that can help solve problems and watching to the Confession film and take a note that shows an inner conflict. The data analysis method used is a qualitative descriptive method where the data is described not in the form of numbers and reduced as needed to find a solution to the problem. The results obtained indicate that the inner conflict experienced by Moriguchi Yuuko is an avoidance-avoidance conflict and an approach-avoidance conflict.